2015
DOI: 10.4103/0974-1208.158617
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte retrieval at 140-mmHg negative aspiration pressure: A promising alternative to flushing and aspiration in assisted reproduction in women with low ovarian reserve

Abstract: BACKGROUND:Oocyte retrieval in women with low ovarian reserve is challenging and often results in poor pregnancy outcomes.AIM:The aim was to compare outcomes of oocyte retrieval using three aspiration methods in women with normal and low antral follicle counts (AFCs).STUDY DESIGN:Retrospective cohort study.SETTING:Tertiary care hospital.MATERIALS AND METHODS:Data from 172 women who underwent in-vitro fertilization/intracytoplasmic sperm injection over 3 years was studied after dividing into three groups: Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It is not uncommon to have no oocytes retrieved in women with severe DOR undergoing IVF, especially when there is very little follicular growth (Karande 2003). In these situations, there are usually no oocytes retrieved despite apparently normally growing ovarian follicles with adequate estradiol (E2) concentrations using meticulous repeated follicular aspiration and flushing (Kumaran et al 2015). Patients with poor prognosis also tend to have high cancellation rates, along with lower pregnancy and live birth rates (Reed et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is not uncommon to have no oocytes retrieved in women with severe DOR undergoing IVF, especially when there is very little follicular growth (Karande 2003). In these situations, there are usually no oocytes retrieved despite apparently normally growing ovarian follicles with adequate estradiol (E2) concentrations using meticulous repeated follicular aspiration and flushing (Kumaran et al 2015). Patients with poor prognosis also tend to have high cancellation rates, along with lower pregnancy and live birth rates (Reed et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no conclusion on the optimal aspiration pressure level, and a variety of pressures between 100 and 200 mmHg are used, often based on manufacturer’s instructions (Panayotidis, 2017; American Institute of Ultrasound in Medicine, 2017). In a single study, higher pressures (140 mmHg) were not associated with damage to the oocytes (Kumaran et al., 2015). The suction pump should be validated prior to use, and a spare suction pump should be available in case one does not work.A stable pressure should be maintained during the procedure, as changes can induce turbulence.…”
Section: Recommendationsmentioning
confidence: 87%
“…At present, there is no conclusion on the optimal aspiration pressure level, and a variety of pressures between 100 and 200 mmHg are used, often based on manufacturer’s instructions (Panayotidis, 2017; American Institute of Ultrasound in Medicine, 2017). In a single study, higher pressures (140 mmHg) were not associated with damage to the oocytes (Kumaran et al., 2015).…”
Section: Recommendationsmentioning
confidence: 87%
“…In addition, the oocyte size is smaller than the needle diameter, and due to different shear stresses, the oocyte comlex may be bounced inside the lumen. It was shown that higher pressure and thicker needles can damage the cumulus-oocyte-complex and was suggested to have great effect on oocyte and embryo quality and reduce the blastulation rate [ 16 , 17 , 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%